Implication for office environment ergonomic intervention: a study of local government offices in Katsina State of Nigeria - Gambo, Abdu (2017)
Work-related musculo-skeletal disorders among the office workers are issues of global concern as they account for over 40% of work place safety and health hazards. In Nigeria, back pains and upper extremities disorder as well as eyes syndrome are common epidemics among the office workers in the Nigerian Public Sector with negative effects on the workers, output and the economy in general. The main objective of this research is to investigate the cases of work related musculo-skeletal disorders among the workers of Local Government offices in Katsina State of Nigeria in relation to the nature of office facilities, nature of office ergonomic policy and ergonomic awareness of the workers. Questionnaire approach was adopted based on 5 Likert scales. Qualitative approach using structured-unobtrusive observation was also adopted to support the fmdings of the questionnaire method. Thus, 250 questionnaires were distributed to 10 Local Governments out of 34 Local Governments of the state using randomised cluster sampling. 218 questionnaires were retrieved representing 86.55% mean response rate, while 210 were ready for the analysis. From the survey of the workers' opinion and the observation of office ergonomic risk factors, it was found that there is a prevalence of work related musculo-skeletal disorders among the workers in Katsina State Local Government offices based on the mean opinion of 3.38, poor office facilities based on the mean opinion of 2.49, poor ergonomic policy based on the mean opinion of 2.35 and poor ergonomic awareness based on the mean opinion of 2.48. Similarly, the result of correlational analysis of the three elements of office ergonomic intervention (office facilities, office ergonomic policy and office ergonomic awareness) shows positive relationship of r=0.545, r=0.441 and r=0.44 respectively. It is therefore concluded that in order to solve the problem of work related musculo-skeletal disorders among the staff of Local Government offices in Katsina State of Nigeria, the three elements of ergonomic intervention must be improved at once in order to achieve sustainable office work environment for the overall productivity of \lvorkers.